1996
DOI: 10.1136/bmj.313.7048.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of common health symptoms with bullying in primary school children

Abstract: Health professionals seeing primary schoolchildren who present with headaches, tummy ache, feeling sad or very sad, bed wetting, and sleeping difficulties should consider bullying as a possible contributory factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
219
0
17

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(257 citation statements)
references
References 5 publications
(8 reference statements)
18
219
0
17
Order By: Relevance
“…This adds depth to the previous literature that supports a connection between bullying, suicide, and depression. 1,[43][44][45][46][47][48][49][50][51][52][53][54] Victims have significantly lower academic achievement in school than bystanders using an objective measure of achievement. 4 Whether the lower academic achievement among victims preceded or was a consequence of being a victim cannot be determined from this cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…This adds depth to the previous literature that supports a connection between bullying, suicide, and depression. 1,[43][44][45][46][47][48][49][50][51][52][53][54] Victims have significantly lower academic achievement in school than bystanders using an objective measure of achievement. 4 Whether the lower academic achievement among victims preceded or was a consequence of being a victim cannot be determined from this cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this is the first study that reveals a relation between being bullied and suicidal ideation at this early age. Previous studies among primary school children in Ireland, 9 Australia, 10 United Kingdom, 11 and Finland 12 also reported that victims of bullying had more depression symptoms than nonvictims. Despite the negative effect of bullying on mental health, many victimized children do not talk about it at home or report it to their teachers.…”
Section: Being Bullied and Psychosocial Healthmentioning
confidence: 97%
“…2,3,6 Bullying has a negative impact on psychosocial health. Being repeatedly bullied has been associated with an increased risk of depression, [7][8][9][10][11][12][13] suicidal ideation, 8 and loneliness. 14 Being a bully is also associated with poorer health outcomes.…”
mentioning
confidence: 99%
“…Indeed, both family disorganization and maternal depression have been shown to correlate moderately with both sleep disturbance and anxiety symptoms in 3--4 year old children and accounted for some of the association between the two difficulties (Gregory et al 2005b). Other candidate environmental influences include being a bully victim, which is associated with poor sleep and feeling sad (Williams et al 1996) and socioeconomic status which is associated with poor sleep and a whole host of other difficulties (Buckhalt et al 2007;Miech et al 1999;Bøe et al 2012). The role of parenting in sleep development and sleep disturbances has been repeatedly demonstrated, particularly in early childhood (Sadeh et al 2010).…”
Section: Sleep and Emotional Difficulties: Links Between Sleep And Emmentioning
confidence: 99%